Biotechnology and species development in aquaculture - S. O. Ayoola; A. A. Idowu (Advances in Aquaculture and Fisheries Management, 2020)
The use of biotechnology in various aspects of human endeavour have obviously created a great impact but not without some risks. Not withstanding, there is still the need for its adoption as more of the already adopted biotechnologies are being improved upon with lesser demerits. Aquaculture is not also left out in the application of biotechnological approaches. The aquaculture industry is currently faced with solving the simultaneous problems of developing economically viable production systems, reducing the impact on the environment and improving public perception. Whereas significant progress has been made in understanding production systems, improvement in cultured stocks has not kept pace with productivity demands. This paper considered aquaculture as the only way to increase fish production and also discusses technical environmental and management considerations regarding the use of genetically modified fish organism (e.g. fish) in aquaculture. This paper discusses advantage of biotechnological research application and commercialization.